2016
DOI: 10.18632/oncotarget.11824
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of weekly cisplatin versus three weekly cisplatin chemotherapy plus concurrent radiotherapy (CRT) for advanced head and neck cancer (HNC)

Abstract: PurposeThis study was performed to compare the efficacies and acute toxicities in weekly- and three weekly- cisplatin based concurrent chemoradiotherapy (CCRT) for advanced HNC patients.Results779 patients of 10 studies were eligible. No difference in the 2-, 3-year OS or 1-, 2-year LRFS was observed, whereas patients in three weekly CCRT arm tended to have a better 5-year OS (HR=1.79, 95%C 0.97-3.31, p=0.06). Weekly arm seemed to show less gastrointestinal toxicities (RR=0.59, 95%CI 0.34-1.02, p=0.06), but si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
(87 reference statements)
1
26
1
Order By: Relevance
“…Only randomized study comparing low (30 m/m 2 ) versus high dose (100 mg/m 2 ) cisplatin prospectively found inferior locoregional disease control with low dose cisplatin. While other studies revealed inferior overall survival with low‐dose cisplatin compare to high‐dose cisplatin . Despite the controversy of high and low dose cisplatin, 15% of LAHNSCC patients in the United States receive weekly low‐dose cisplatin with radiation according to LORHAN analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Only randomized study comparing low (30 m/m 2 ) versus high dose (100 mg/m 2 ) cisplatin prospectively found inferior locoregional disease control with low dose cisplatin. While other studies revealed inferior overall survival with low‐dose cisplatin compare to high‐dose cisplatin . Despite the controversy of high and low dose cisplatin, 15% of LAHNSCC patients in the United States receive weekly low‐dose cisplatin with radiation according to LORHAN analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin was used for metastatic cutaneous squamous cell carcinoma and yielded an overall response rate of 45% and prolonged disease-free survival [ 8 ]. Cisplatin was also suitable for treating non-nasopharyngeal carcinoma, and every three weekly chemotherapy strategy yielded better 5-year overall survival outcomes as compared to a weekly chemotherapy strategy [ 9 ]. Cisplatin is used for most patients with NSCLCs and forms the basis of first-line chemotherapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are currently four meta-analyses/systematic reviews (Table 1) that should have provided a detailed, both quantitative and qualitative, synthesis of the existing data. [4][5][6][7] The data from the most recent study by Sturz et al from 2019 [8] are the same as ones published originally in 2017. [5] Different time periods focused upon in these meta-analyses naturally resulted in a different number and type of studies included (main and separate analysis), and consequentially a different patient number, unfortunately not always specified.…”
Section: Introductionmentioning
confidence: 67%
“…In spite of these shortcomings, it is remarkable to observe that there is no significant difference in not only OS, but LRFS, PFS, and RR as well. Regarding toxicity, while Guan et al [4] and Mohamed et al [7] found no difference in any of documented toxicities, Jacinto et al [6] found Grade >3 mucositis significantly more frequent in weekly CDDP, but only in a single RCT (using postoperative RT-CHT), while there was no difference in six retrospective studies using concurrent RT-CHT alone. In Sturz et al [5], the administration of CDDP every 3 weeks led to significantly more leucopenia, neutropenia, N&V and nephrotoxicity, with no difference in incidence rates of stomatitis and mucositis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation